Investigations into the asymmetric synthesis and biological activities of some bisbenzyltetrahydroisoquinoline alkaloids - Ralph, Mark S., 1977- (2001)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2002. Chemistry Bibliography: leaves 108-112 Bisbenzyltetrahydroisoquinoline (BBIQ) alkaloids are a very large and structurally diverse family of compounds that have been isolated from a variety of plant sources and have been found to exhibit a multitude of pharmacological properties including antitumor, antimalarial, and antibacterial activities. Variations in the number of aromatic oxygen substituents present, the number of ether linkages, the nature of the ether bridges and the sites on the two benzylisoquinoline units where the ether or carbon-carbon bond originate, have made BBIQs very interesting targets for several synthetic endeavours. -- The research described herein will focus on the anti-inflammatory and antioxidant activities of the BBIQ oxyacanthine and several other compounds isolated from the herbal plant Mahonia aquifolium using the lipoxygenase inhibition and DPPH radical scavenging assays. In addition, the total synthesis of two target BBIQ are investigated utilizing the Pictet-Spengler and Bischler-Napieralski strategies for isoquinoline formation. Furthermore, alternative means to the classic Ullmann conditions for ether linkages is explored.